Root canal morphology of maxillary premolars - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 1998)
The objective of this study was to investigate further internal anatomy of maxillary premolars. Six hundred recently extracted maxillary first and second premolar teeth were used in this study, One-half of the teeth were maxillary first premolars, the other half were maxillary second premolars. The teeth were stored in 10% formalin solution, and a standard clearing technique was applied with some modifications. Finally, ink-dyed root canal systems were evaluated by a dissecting light microscope, Each tooth was examined as to the number of roots and root canals and their types, ramifications of the main root canals, and location of apical foramina and transverse anastomoses, Examination of the root canal systems of the teeth was based on Vertucci's classification. The incidence of type I canals (one canal) for the maxillary first premolars was 8.66%, whereas 89.64% of the total samples demonstrated two canals (from type II to type VII), Only 1.66% of maxillary first premolars were type VIII or type IX (three canals). Regarding maxillary second premolars, the incidence of type I (one canal) was 48.66%, whereas it was 50.64% for type II to type VII (two canals), Type VIII (three canals) was found in 0.66% of the total sample.